Analisa kekuatan mekanis komposit serat kelapa dengan polyvinyl chloride (PVC) untuk body Go-Kart - Dward Dabble Taliak (Publikasi Indonesia, 2025)
This study aims to analyze the mechanical strength of coconut fiber composites with epoxy resin as an alternative material for go-kart bodies. Coconut fiber was selected due to its availability, low cost, and eco-friendly properties. The experimental method used fiber-to-resin ratios of 80:20, 70:30, and 60:40. The specimens were tested through bending tests, Charpy impact tests, and Vickers hardness tests. The results indicated that the 70:30 ratio provided the highest bending strength of 21.18 N/mm² and the highest average hardness of 166 VHN, while the 60:40 ratio produced the highest impact energy of 0.623 J/mm². The 80:20 ratio showed the lowest values across all parameters. These findings confirm that variations in coconut fiber fractions significantly affect the mechanical properties of the composites. Overall, the 70:30 ratio demonstrated the most balanced mechanical performance and is recommended as an alternative material for go-kart bodies, offering enhanced strength, lightweight properties, and environmental sustainability.